Optimal Decision-making on Charging of Electric Vehicles - Xin Gong; Tao Lin (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Large-scale development of electric vehicles (EVs) will have a significant impact on the power grid with their great demand for electric power consumption. It is necessary to design the optimal charging scheme for EVs. In this paper, we propose a centralized and a decentralized scheme of optimal decision-making on charging of EVs based on a dynamic pricing model. The objective of both schemes is to minimize the costs of EVs by establishing EV charging optimal schedules that fills the overnight load valley.The centralized scheme,whose objective is to minimize the total charging costs of all EVs, determines the charging schedules of EVs through solving a global optimization problem by the utility.The decentralized scheme is based on congestion game theory,under which the charging schedules are determined locally and directly by EVs to minimize their own costs. Detailed mathematical models and solution procedures are presented for both the centralized and decentralized schemes. Results show that both schemes have good performance on valley-filling. DOI : http://dx.doi.org/10.11591/telkomnika.v12i4.4098